Blood flow restriction as a post-exercise recovery strategy: A systematic review of the current status of the literature - M. Oliva-Lozano, José; Patterson, Stephen D.; Chiampas, George; Maybury, Ellie; Cost, Rick (Biology of Sport, 2024)
The aim of this study was to systematically review the current literature on blood flow restriction (BFR) as a post-exercise recovery strategy. Experimental studies investigating the effect of BFR on recovery after exercise were included. Only studies meeting the following inclusion criteria were selected: (a) studies investigating about BFR as a post-exercise recovery strategy in athletes and healthy individuals; (b) the full text being available in English; (c) experimental research study design. Studies that exclusively analyzed BFR as a recovery strategy during the exercise (e.g., recovery strategy between bouts of exercise) were excluded. A literature review was conducted on the PubMed, Cochrane, and Web of Science electronic databases up until May 7 th , 2023. The main findings were that (i) 9 studies investigated passive BFR as a post-exercise recovery strategy, which shows a significant lack of research in both team and individual sports (especially in female populations), and only 2 studies used active BFR protocols; (ii) although a high quality range of studies was observed, there were methodological limitations such as BFR interventions that were usually conducted after fatiguing protocols or fitness tests, which may not represent the real exercise (e.g., a sprint session of 6 sets of 50 m may induce muscle damage but it does not represent the demands of a team sport like rugby or soccer); (iii) there is a lack of consistency in BFR protocols (e.g., number of cycles or duration of the occlusion-reperfusion periods) for recovery; (iv) some studies showed beneficial effects while others found no positive or detrimental effects of BFR as a post-exercise recovery strategy in comparison with the control/SHAM group. In conclusion, only 11 studies investigated BFR as a post-exercise recovery strategy and there is not any significant amount of evidence in team or individual sports (especially in female populations). BFR could be a potential post-exercise recovery strategy, but practitioners should use caution when applying this method of recovery for their athletes and clients. In addition, it would be of interest for high performance-related practitioners to have a better understanding of the benefits of BFR interventions combined with either active or passive forms of exercise as a post-exercise recovery strategy.